European Union : Publication of Financial Sector Assessment Program Documentation -- Technical Note on European Insurance and Occupational Pensions Authority Assessment. (IMF Staff Country Reports; Country Report ;, 2013)
Slow economic growth and continuing low interest rate environment is putting pressure on the insurance sector. Delays in the implementation of Solvency II could create vulnerabilities in the insurance sector. The approval of internal models is important for determining adequacy of capital levels to warrant a solvent industry. The new European system of financial supervision has been proactive, but much work has to be done. Access to information for monitoring, analyzing trends, and preventing systemic risk need to improve, along with operational independence.